Analysis of the Relationship Between Knowledge, Perception, and Workload of Nurses on Patient Safety Culture - Norsehan Norsehan; Ratno Adrianto; Rahmat Bakhtiar; Irfansyah Baharuddin Pakki; Hilda Hilda (GLOBAL HEALTH SCIENCE GROUP, 2025)
Patient safety culture refers to a pattern of behavior of both individuals and organizations that consistently seek to reduce the risk of harm or injury to patients due to the services provided, based on shared beliefs and values. This study aims to analyze the relationship between knowledge, perceptions, and workload of nurses on patient safety culture at Beriman Hospital, Balikpapan City. The method used in this study is a quantitative approach with a cross-sectional design, involving all nurses working in the service unit of Beriman Hospital, Balikpapan City, totaling 129 respondents (total sampling). This study was conducted from February to March 2025, with data collection using a questionnaire that had been tested for validity and reliability. Univariate data analysis, chi-square test, and logistic regression. The results showed good knowledge 81.4%, good perception 51.2%, high workload 50.4% and patient safety culture value 58.9%. The results of the chi-square test sig value of knowledge: 0.600 and perception: 0.302, both (p> 0.05) indicating no relationship between knowledge and perception of nurses towards patient safety culture. However, the sig value for workload is 0.006 (p <0.05) indicating a relationship between workload and patient safety culture. The results of the logistic regression test show that nurses' workload has a significant effect on patient safety culture with a significance value (Sig) of 0.009. The Odds Ratio (OR) value of 2.712 indicates that nurses with a higher workload are 2.7 times more likely to influence patient safety culture compared to those with a low workload. The conclusion is that workload is the factor most related to patient safety culture.